Vice and the Victorians - Huggins, Mike (Bloomsbury Academic, 2016)
"Vice and the Victorians explores the ways the Victorian world gave meanings to the word 'vice', and the role this complex notion played in shaping society. Mike Huggins provides a richer and more nuanced understanding of a term that, despite its vital importance to the Victorians, has thus far lacked a clear definition. Each chapter explores a different facet of vice. Firstly, the book seeks to define exactly what vice meant to the Victorians, exploring how the language of vice was used as a tool to beat down opposition and dissent. It considers the cultural geography and spatial dimensions of vice in the public and private spheres, before moving on to look at specific vices: the unholy trinity of drink, sex and gambling. Finally, it shifts from vice to virtue and the efforts of moral reformers, and reassesses the relationship between vice and respectability in Victorian life. In his lively and engaging discussion, Mike Huggins draws on a range of theory and exploits a wide variety of texts and representations from the periodical press, parliamentary reports and Acts, novels, obscene publications, paintings and posters, newspapers, sermons, pamphlets and investigative works. This will be an illuminating text for undergraduates studying Victorian Britain as well as anyone wishing to gain a more nuanced understanding of Victorian society."--Bloomsbury Publishing